Appearance of a population of the mangrove rail Rallus longirostris (Rallidae) in salt marshes invaded by the exotic tanner grass Urochloa arrecta (Poaceae) and its disappearance after plant management - Bornschein, Marcos R. [UNESP]; Teixeira, Larissa [UNESP]; de Morais Guerra, Bruno [UNESP]; Melchiori, Bianca L. [UNESP]; Reinert, Bianca L. [UNESP]; Sandretti-Silva, Giovanna [UNESP] (Springer Nature, 2022)
Biological invasions cause species extinction but can also provide benefits. Wetlands, such as salt marshes, include little-known but important ecosystems that are sometimes severely invaded by exotic plants. Salt marshes in eastern South America are increasingly impacted by invasions of the African grass Urochloa arrecta. This study investigated the appearance of a population of the mangrove rail Rallus longirostris in areas dominated by U. arrecta and its disappearance with the eradication of this plant. We monitored four areas (54.47 ha) in the Guaratuba Bay estuary in southern Brazil, from 2006 to 2022, two of which contained four patches of U. arrecta as the dominant species. In 2012, we started to eradicate U. arrecta with mechanical management, and in 2020, it was eradicated locally. We recorded R. longirostris for the first time within a patch of U. arrecta in 2007. In subsequent years we saw the species in two other patches of the exotic plant. Rallus longirostris was no longer observed once U. arrecta was eradicated. Differences in patch occupancy between invaded and uninvaded habitats observed for R. longirostris and Pardirallus nigricans, and the disappearance of R. longirostris following the exotic plant management suggest competitive advantage and/or differential habitat preference and population density as hypotheses to explain observed patterns. The invasion of U. arrecta can increase the local populations of R. longirostris. Since this bird is not endangered, we encourage the management of U. arrecta because of its impact on salt marshes, including an endemic endangered bird.
Keywords: Competition; Ecological trap; Estuary; Nesting site; Pardirallus nigricans; Restoration